Kosovo and the Evolution of State Sovereignty - Gary Schaub, Jr (Refuge, 1999)
The author argues that NATO's intervention in response to the Yugoslav government's repression in Kosovo may accelerate theinternational community's acceptance of the liberal-democratic nation of popular sovereignty over the Westphalian notion of state sovereignty. The tension between these rival conceptions, planted in the UN Charter itself, gestated throughout the Cold War. Unlike the incremental steps toward accepting notions of popular sovereignty taken by the international community since the Cold War's end, NATO's Kosovar intervention has brought this rivalry into bold relief. Will the wider international community accept the West's conception of popular sovereignty? Although initial indications are good, wide acceptance is contingent upon NATO's success in Kosovo - and even then, only time will tell.